2002
DOI: 10.1086/324783
|View full text |Cite
|
Sign up to set email alerts
|

Orbits of Four Very Massive Binaries in the R136 Cluster

Abstract: We present radial velocity and photometry for four early-type, massive double-lined spectroscopic binaries in the R136 cluster. Three of these systems are eclipsing, allowing orbital inclinations to be determined. One of these systems, R136-38 (O3 V + O6 V), has one of the highest masses ever measured, 57 Mo, for the primary. Comparison of our masses with those derived from standard evolutionary tracks shows excellent agreement. We also identify five other light variables in the R136 cluster which are worthy o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 33 publications
(48 reference statements)
3
83
0
Order By: Relevance
“…Rotating stars are dimmer because of the reduced internal pressure. Mass loss and rotation also alter the MLR for intermediate and especially high-mass stars (16). The IMF follows by correcting the observed number of main sequence stars for the number of stars that have evolved off the main sequence.…”
Section: The Form Of the Imfmentioning
confidence: 99%
“…Rotating stars are dimmer because of the reduced internal pressure. Mass loss and rotation also alter the MLR for intermediate and especially high-mass stars (16). The IMF follows by correcting the observed number of main sequence stars for the number of stars that have evolved off the main sequence.…”
Section: The Form Of the Imfmentioning
confidence: 99%
“…They obtained FOS spectroscopy of all the bright point sources in the core and combined it with PC (WFPC2) photometry to derive a color-magnitude diagram of the massive stars. In a follow-up paper, Massey et al (2002) observed four spectroscopic eclipsing binaries and measured their masses. They also detected another five eclipsing binaries, indicating that massive binaries are also common in R136.…”
Section: R136mentioning
confidence: 99%
“…HST observations of Mk 34 show photometric variability of a few tenths of a magnitude over a period of 20 days (Massey et al 2002). Mk 34 was known to be X-ray bright from ROSAT data ( Wang 1995).…”
Section: Melnick 34 and Other Wn5h Starsmentioning
confidence: 99%